Designing a vehicle driving simulator: mechanical and electrical parts - Nguyễn Bá Hải; Phan Ngọc Trung (Journal of Technical Education Science, 2012)
This research focuses on designing a driving simulator and selecting electrical and electronic components such as sensors for measuring handwheel rotation, actuators for displaying force-feedback, DAQ board for interfacing sensors and actuator with a computer, and so on. This paper also presents the literature review of driving simulators. The proposed design and selected components offer a low cost solution for developing driving simulators for Viet Nam